2005
DOI: 10.2298/avb0506413l
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalohippocampal area in adult male rats after progesterone treatment

Abstract: Neurons of amygdalohippocampal area (AHA) of the amygdaloid complex (AC) in adult control and progesterone (P) neonatally treated adult male rats were studied using light microscopy and morphometric analysis. Progesterone in a single dose of 1.25 mg was administered at the age of 5 days (neonatal period) and in a dose of 5 mg at 30 days of age. Two stereological parameters were estimated: the volume density (VJ (mm0) AHA cell nuclei cytoplasm, neuropil and the numerical density (NJ (mm3) of neurons. In adult, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Our previous studies have indicated the importance of the postnatal period in the development of the central nervous system [12][13][14][15]. In the postnatal periods in the rat CP as BCSFB continues to grow to reach its maturity [16], but the period of this maturation differs considerably among mammalian species [17].…”
Section: Introductionmentioning
confidence: 98%
“…Our previous studies have indicated the importance of the postnatal period in the development of the central nervous system [12][13][14][15]. In the postnatal periods in the rat CP as BCSFB continues to grow to reach its maturity [16], but the period of this maturation differs considerably among mammalian species [17].…”
Section: Introductionmentioning
confidence: 98%